2010
DOI: 10.1093/mp/ssp119
|View full text |Cite
|
Sign up to set email alerts
|

The Sulfate Transporter Family in Wheat: Tissue-Specific Gene Expression in Relation to Nutrition

Abstract: Sulfate uptake and distribution in plants are managed by the differential expression of a family of transporters, developmentally, spatially, and in response to sulfur nutrition. Elucidation of the signaling pathways involved requires a knowledge of the component parts and their interactions. Here, the expression patterns of the full complement of sulfate transporters in wheat, as influenced by development and sulfur nutrition, are described. The 10 wheat sulfate transporters characterized here are compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 38 publications
3
51
1
Order By: Relevance
“…The low-affinity sulfate transporters AtSULTR2;1 and AtSULTR2;2 have also been found to catalyze Se uptake into the stele cells, and the activity of AtSULTR2;1 can be positively regulated by the AtSULTR3;5 that does not directly catalyze Se transport [72]. Additionally, increased Se availability can induce the expression of SULTR2;1 and SULTR2;2 in Arabidopsis [60,73,74]. Intriguingly, the transcription levels of SULRT2 are greater in the roots of Se hyperaccumulator species than non-Se hyperaccumulator species, indicating that high-level expression of SULRT2 contributed to the increased Se flux from roots to shoots in the hyperaccumulator species [75].…”
Section: Bf06 Vocs Regulates Plant Uptake Of Se By Upregulating Of Sumentioning
confidence: 99%
“…The low-affinity sulfate transporters AtSULTR2;1 and AtSULTR2;2 have also been found to catalyze Se uptake into the stele cells, and the activity of AtSULTR2;1 can be positively regulated by the AtSULTR3;5 that does not directly catalyze Se transport [72]. Additionally, increased Se availability can induce the expression of SULTR2;1 and SULTR2;2 in Arabidopsis [60,73,74]. Intriguingly, the transcription levels of SULRT2 are greater in the roots of Se hyperaccumulator species than non-Se hyperaccumulator species, indicating that high-level expression of SULRT2 contributed to the increased Se flux from roots to shoots in the hyperaccumulator species [75].…”
Section: Bf06 Vocs Regulates Plant Uptake Of Se By Upregulating Of Sumentioning
confidence: 99%
“…3, A and B). Previously, such high-affinity group 1 STs were characterized as being responsible for the primary uptake of sulfate by the root (Buchner et al, 2010). However, several studies also showed the presence of their transcripts in shoots of S-deficient plants, suggesting a further function for S distribution into different cell types in different tissues (Koralewska et al, 2007;Ciaffi et al, 2013).…”
Section: Determination Of Metabolite Levelsmentioning
confidence: 99%
“…Specific gene expression values were normalized to the actin2 or proteasome subunit family protein expression value, and relative values (with respect to the 2S at the first time point measured for any specific tissue) are presented. A comparison of absolute expression levels for the different transporters in different wheat tissues is presented by Buchner et al (2010).…”
Section: Semiquantitative Reverse Transcription-pcrmentioning
confidence: 99%
“…Genome analysis and systematic cloning studies indicate that wheat, Brassica oleracea, and rice (Oryza sativa) have similar sulfate transporter gene groups, and it is probable that close homologs have similar functions (Buchner et al, 2004a(Buchner et al, , 2004c(Buchner et al, , 2010. The phylogenetic relationships of Arabidopsis and wheat sulfate transporters are shown in Figure 1.…”
mentioning
confidence: 99%